2020
DOI: 10.1016/j.cyto.2019.154894
|View full text |Cite
|
Sign up to set email alerts
|

Distinct inflammatory mediator patterns in young black and white adults: The African-predict study

Abstract: Objective: Inflammatory mediators have been implicated in the early stages of cardiovascular disease development, including hypertension. Since global reports reflect a higher hypertension prevalence in black than white populations, we hypothesise the involvement of specific inflammatory mediators. We therefore compared a detailed range of 22 inflammatory mediators between young black and white adults, and determined the relationship with blood pressure. Approach and Results: We included 1197 adults (20-30 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 61 publications
3
10
1
Order By: Relevance
“…This discrepancy may lie in the fact that most of these other cohorts were examined in relation to cardiovascular‐related disease or events. IFN‐γ was higher among our White study participants, consistent with findings in another study 52 . In contrast, other investigators found that African–American women had significantly higher mean levels of IFN‐γ then White women 70 .…”
Section: Discussionsupporting
confidence: 91%
“…This discrepancy may lie in the fact that most of these other cohorts were examined in relation to cardiovascular‐related disease or events. IFN‐γ was higher among our White study participants, consistent with findings in another study 52 . In contrast, other investigators found that African–American women had significantly higher mean levels of IFN‐γ then White women 70 .…”
Section: Discussionsupporting
confidence: 91%
“…The black and white groups were similar in age (24.5 years; p = 0.92) with an equal distribution in sex (p = 0.71). When viewing the detailed inflammatory mediator profile of the two groups, the black group had higher pro-to-anti-inflammatory ratios than their white counterparts (p ≤ 0.021) as was seen in a previous study in this population [17]. There were no ethnic differences for Na + excretion (p = 0.47), but black participants had lower urine levels of K + , with 94% black and 88% white participants having K + levels below recommended levels [28].…”
Section: Resultssupporting
confidence: 63%
“…Previous studies also reported a greater proportion of salt sensitivity in black populations [16]. The cardiovascular risk in black populations may be further increased based on their more pro-inflammatory profile when compared to white adults [17].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations